Synaptic NR2A- but not NR2B-containing NMDA receptors increase with blockade of ionotropic glutamate receptors - Von Engelhardt, Jakob; Doganci, Beril; Seeburg, Peter H.; Monyer, Hannah (Frontiers in Molecular Neuroscience, 2009)
NMDA receptors are key molecules involved in physiological and pathophysiological brain processes such as plasticity and excitotoxicity. Neuronal activity regulates NMDA receptor levels in the cell membrane. However, little is known on which time scale this regulation occurs and whether the two main diheteromeric NMDA receptor subtypes in forebrain, NR1/NR2A and NR1/NR2B, are regulated in a similar fashion. As these differ considerably in their electrophysiological properties, the NR2A/NR2B ratio affects the neurons’ reaction to NMDA receptor activation. Here we provide evidence that the basal turnover rate in the cell membrane of NR2A- and NR2B-containing receptors is comparable. However, the level of the NR2A subtype in the cell membrane is highly regulated by NMDA receptor activity, resulting in a several-fold increased insertion of new receptors after blocking NMDA receptors for 8 hours. Blocking AMPA receptors also increases the delivery of NR2A-containing receptors to the cell membrane. In contrast, the amount of NR2B-containing receptors in the cell membrane is not affected by ionotropic glutamate receptor block. Moreover, electrophysiological analysis of synaptic currents in hippocampal cultures and CA1 neurons of hippocampal slices revealed that after 8 hours of NMDA receptor blockade the NMDA EPSCs increase as a result of augmented NMDA receptor-mediated currents. In conclusion, synaptic NR2A- but not NR2B-containing receptors are dynamically regulated, enabling neurons to change their NR2A/NR2B ratio within a time scale of hours.